Keyhole Mini-Craniotomy Middle Fossa Approach for Tegmen Repair: A Case Series and Technical Instruction - Adil, Syed M.; Zachem, Tanner J.; Hatfield, Jordan K.; Abdelgadir, Jihad; Hoang, Kimberly; Codd, Patrick J. (Journal of Neurological Surgery Reports, 2025)
Background and Importance Tegmen defects associated with cerebrospinal fluid (CSF) leaks are a rare pathology that can result in severe complications if left untreated. There is no universal optimal surgical algorithm for repair, although the most common techniques are the middle fossa craniotomy (traditionally 25 cm2 in area), the transmastoid approach, or both. Here, we describe successful use of a keyhole mini-craniotomy, only 6 cm2 in area, without mastoidectomy or days of lumbar drainage.Clinical Presentation Three patients presented with right-sided CSF otorrhea and hearing loss, with varying sizes of tegmen defects and associated encephaloceles. Keyhole craniotomies measuring 3 × 2 cm were used to perform a multilayer repair comprising an intradural collagen dural substitute, extradural fascial graft, extradural collagen dural substitute, fibrin sealant, and sometimes bony reconstruction using partial thickness craniotomy grafting. All patients were discharged on postoperative day 1 or 2, with no recurrence of symptoms at 6 months.Conclusion The keyhole craniotomy approach does not sacrifice the extent of operative access for this pathology. This minimally invasive approach can likely be used more often without need for concomitant mastoidectomy, ultimately enabling shorter hospital stays and more rapid recovery.
Keywords: cerebrospinal fluid leak; keyhole craniotomy; middle cranial fossa approach; mini-craniotomy; minimally invasive; otorrhea; tegmen defect